Analysis of prescription pattern of anemia in pregnancy: an observational, cross-sectional study - Amrale, Prasad R.; Ahire, Sagar S.; Vairage, Reshma M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Anemia is a major health problem that affects 25% to 50% of the population of the world and approximately 50% of pregnant women. This research on the use of prescription medicines in anemia during pregnancy remains critically important. Prescribing patterns of the drug in the pregnant women include age, trimester, gravid condition, US-FDA risk category, WHO core indicators. Methods: A prospective, cross sectional observational multicentric study was conducted in outpatient and inpatient departments of Indira Gandhi Hospital and Civil Hospital in Nasik, for period of 6 months. Ethical approval was taken prior to study from Independent ethics committee. A total of 197 patients were enrolled in the study. Inform consent form was obtained from the patients. After studying them; statistical analysis were done and result and conclusion were drawn. Results: Out of 197 women’s prescriptions, the average number of drug per prescription was 2.14. 27.28% drugs were prescribed there brand name and 72.72% by generic name. Iron, folic acid and calcium were prescribed to all pregnant women. The majority of the patients were prescribed category A and category C drugs. No patients were given category X drug. Conclusions: Nearly all prescription showed a prescribing practice for writing prophylactic iron and folic acid therapy in all pregnant women. No women was prescribed category X drug. Most of the drug prescribed in generics and thus, prescription pattern of our study set a fine example of prescribing behaviour.